WHY SARCOPENIC OBESITY IS THE STRATEGIC INTERSECTION? – A NARRATIVE REVIEW - Słowik, Michał; Świercz, Jędrzej; Arciszewski, Kamil; Hariasz, Natalia; Orda, Karolina; Walczak, Dominika; Szumiło, Jakub; Kaspersk, Klaudia; Markiv, Mariana; Stenzel, Paweł (International Journal of Innovative Technologies in Social Science, 2026)
Sarcopenic obesity has emerged as a significant clinical and public health concern due to the simultaneous presence of decreased skeletal muscle mass and increased adipose tissue accumulation. This condition represents a complex metabolic state that combines the adverse consequences of both sarcopenia and obesity, leading to deterioration of physical function and metabolic health.The purpose of this review is to analyze current scientific evidence regarding the epidemiology, pathophysiological mechanisms, diagnostic challenges, and clinical consequences of sarcopenic obesity, as well as potential therapeutic and preventive strategies. A narrative review of studies published between 2000 and 2025 using PubMed, Scopus, and Web of Science was conducted.The findings indicate that sarcopenic obesity is associated with aging, metabolic dysregulation, and lifestyle-related factors such as physical inactivity and inadequate nutrition. Chronic low-grade inflammation, insulin resistance, hormonal alterations, and mitochondrial dysfunction play key roles in its development. Sarcopenic obesity has been associated with an increased risk of cardiovascular diseases, type 2 diabetes, frailty, disability, and mortality.The condition remains underdiagnosed due to the lack of standardized diagnostic criteria and limitations of traditional indicators such as body mass index. Effective management requires a multidisciplinary approach combining resistance exercise, nutritional interventions, and lifestyle modifications. Understanding its mechanisms may improve prevention and clinical management in aging populations.